1 / 25

260 likes | 559 Views

Geometric Sequences. Common ratio 9.3. SAT Prep. Quick poll!. POD preview. Give the first 5 terms of the sequence for a n = a 1 (3) n-1 if a 1 =2 Is this formula recursive or explicit? What is the pattern in this sequence? How do we know?. POD preview.

Download Presentation
## Geometric Sequences

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Geometric Sequences**Common ratio 9.3**SAT Prep**Quick poll!**POD preview**Give the first 5 terms of the sequence for an = a1(3)n-1 if a1 =2 Is this formula recursive or explicit? What is the pattern in this sequence? How do we know?**POD preview**Give the first 5 terms of the sequence for an = a1(3)n-1 if a1 =2 2, 6, 18, 54, 162 This is an explicit formula. Each term is 3 times the previous term.**Geometric sequences**If the pattern between terms in a sequence is a common ratio, then it is a geometric sequence. The ratio is r. Recursive: a1 an = an-1r so, r = an/an-1 What would the explicit formula be?**Geometric sequences**If the pattern between terms in a sequence is a common ratio, then it is a geometric sequence. The ratio is r. Explicit: an = a1rn-1 (In other words, find the nth term by multiplying a1 by r and do that (n-1) times.)**Geometric sequences**Recursive: a1 an = an-1r so, r = an/an-1 Explicit: an = a1rn-1 How does these compare to the formulas for an arithmetic sequence?**Use it**Find the 10th term of our POD sequence an = 2(3)n-1**Use it**Find the 10th term of our POD sequence an = a1(3)n-1 a10 = 2(3)10-1 = 2(3)9 = 39366**Use it again**If the third term of a geometric sequence is 5 and the sixth term is -40, find the eighth term. Like with arithmetic sequences, we need the first term and the change between terms. Like we did with arithmetic sequences, we start by writing the equations. Now what? -40 = a1(r)6-1 -40 = a1(r)5 5 = a1(r)3-1 5 = a1(r)2**Use it again**If the third term of a geometric sequence is 5 and the sixth term is -40, find the eighth term. Once we have the equations, we can find r. -40 = a1(r)5 5 = a1(r )2 -8 = r3 and r = -2**Use it again**If the third term of a geometric sequence is 5 and the sixth term is -40, find the eighth term. r = -2 Once we have r, we can find a1. 5 = a1 (-2)2 5 = a1 (4) a1 = 5/4**Use it again**If the third term of a geometric sequence is 5 and the sixth term is -40, find the eighth term. r = -2 a1 = 5/4 Once we have r and a1, we can find the equation. an = (5/4)(-2)n-1 And answer the question: a8 = (5/4)(-2)8-1 = (5/4)(-2)7 = (5/4)(-128) = -160**Partial sums**Add the first 8 terms of our POD sequence 2 + 6 + 18 + 54 + 162 + 486 + 1458 + 4374 (And here’s a free vocabulary word: when we add the terms of a sequence, we call it a series. This is a finite geometric series. When we did partial sums of arithmetic sequences, those were also series.)**Partial sums**Add the first 8 terms of our sequence 2 + 6 + 18 + 54 + 162 + 486 + 1458 + 4374 = 6560 How long did that take? Want a shortcut? Not surprisingly, there are formulas.**Partial sums (finite series)**Here’s the bottom line: Check it with our sequence:**Infinite sums (infinite series)**If | r | < 1, then we can determine the sum of the entire geometric series. This is called an infinite series, and we can find the sum only in this particular case.**Infinite sums (infinite series)**An infinite series may be noted using summation notation. If r < 0, we have something called an alternating infinite series. (Why?)**An example of an alternating series**Find the sum of the alternating geometric series It may help to calculate the first couple of terms to verify the first term and r. Then, because | r | < 1, we can find the sum of the infinite series.**A financial example**You want to save money by setting aside a 1 cent the first day, 2 cents the second day, 4 cents the third day, and so on. How much would you set aside on the 15th day?**A financial example**You want to save money by setting aside a 1 cent the first day, 2 cents the second day, 4 cents the third day, and so on. How much would you set aside on the 15th day? A15 = 1(2)15-1 = 214 = 16384 = $163.84**A financial example**You want to save money by setting aside a 1 cent the first day, 2 cents the second day, 4 cents the third day, and so on. How much have you set aside after 30 days?**A financial example**You want to save money by setting aside a 1 cent the first day, 2 cents the second day, 4 cents the third day, and so on. How much have you set aside after 30 days? n = 30**A fraction example**Find a rational number that corresponds to This number can be represented as a sum. 5.4 + .027 + .00027 + .0000027 + …**A fraction example**Find a rational number that corresponds to 5.4 + .027 + .00027 + .0000027 + … The last part looks like a geometric series where r = .01 and a1 = .027 Since r < 1, we can find this infinite sum. And looks like 5.4 + 3/110 = 594/110 + 3/110 = 597/110.

More Related